Love the country and appreciate the value of true patriotism - UMP, PNC (2019)
It is essential for Malaysians to have the spirit of the truest patriotism, one who loves the country and will do whatever it takes, whether it is related to a perception, belief or faith, in order to defend the nation. In the context of Malaysia having a multi-racial society, it is very important for the people to have a sense of patriotism, take pride in being Malaysians and be loyal to the country.